Pengaruh Budaya Organisasi Islam dan Lingkungan Kerja terhadap Kinerja Karyawan Bank Syariah Indonesia (Studi Kasus Bank Syariah Indonesia Kantor Cabang Universitas Jember) - Mohammad Alfi Bima Ghafar Ali (IJABAH, 2023)
A study that describes how much influence Islamic organizational culture and work environment have on employee performance at Bank BSI KCP University of Jember. The research used by researchers is quantitative research and data collection techniques using observation, interviews, documentation and questionnaires to 30 respondents with a non-probability sample using saturated sampling techniques. The results of the statistical regression test on the variables of Islamic organizational culture (X_1) and work environment (X_2) have a positive effect on employee performance (Y). This is shown in the results of multiple linear regression analysis, namely Y=15.102+-0.731 X_1+1.203 X_2+e. The results of testing the hypothesis t test for Islamic organizational culture (X_1) count significant value of 0.020 <0.05 and t_count -2.466 > t_table 2.042 which means Islamic organizational culture (X_1) partially has a negative and significant effect on employee performance, the results for work environment variable (X_2) a significant calculated value of 0.000 <0.05 and t_count 5.074 > t_table 2.042 which means the work environment (X_2) partially has a positive and significant influence on employee performance. Simultaneous statistical test results or the f-test showed f_count = 19.766 > f_table = 3.32 and arithmetic significance of 0.000 <0.05. Keywords: Islamic Organizational Culture, Work Environment and Employee Performance